2012
DOI: 10.1017/s1368980012004375
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of behavioural weight-loss interventions involving primary-care physicians in overweight and obese primary-care patients (1999–2011)

Abstract: Objective: The present review aimed to examine the effectiveness of behavioural weight-loss interventions involving primary-care physicians in producing weight loss in overweight and obese primary-care patients. Design: A systematic review was conducted by searching online databases (MEDLINE, EMBASE, Cochrane, PsycINFO and SCOPUS) from January 1999 to December 2011. All abstracts were screened and coded for eligibility. The Cochrane Effective Practice and Organisation of Care Group quality criteria were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 44 publications
1
24
1
Order By: Relevance
“…diet and exercise) intervention that included dietary advice from a qualified dietician, in line with AHA/ACC/TOS guidelines [7]. It has been reported that dietician-delivered counselling is more effective than physician-delivered outpatient programs, achieving ∼3-6 kg weight loss in individuals with overweight/obesity [20]. Weight loss was expected with placebo as a result of the robust diet and exercise intervention, so it was encouraging the estimated treatment difference between liraglutide and placebo indicated that the additional weight loss achieved with liraglutide was clinically relevant for individuals both without (-5.4% (fig.…”
Section: Discussionmentioning
confidence: 99%
“…diet and exercise) intervention that included dietary advice from a qualified dietician, in line with AHA/ACC/TOS guidelines [7]. It has been reported that dietician-delivered counselling is more effective than physician-delivered outpatient programs, achieving ∼3-6 kg weight loss in individuals with overweight/obesity [20]. Weight loss was expected with placebo as a result of the robust diet and exercise intervention, so it was encouraging the estimated treatment difference between liraglutide and placebo indicated that the additional weight loss achieved with liraglutide was clinically relevant for individuals both without (-5.4% (fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on Delphi and EPOC are similar to previously published results. 80 Due to the nature of this research, blinding was difficult. Studies of higher quality (≥ 7 EPOC criteria) 58,60,62,63,65,67,68,72 reported greater weight loss, an encouraging finding.…”
Section: Discussionmentioning
confidence: 99%
“…124,125 Although rates across individual studies vary widely, 126,127 reviews have found average retention rates of 70-80%. 121,128 A recent study of a mobile BOX 6 Study co-ordinators' experience of the study Benefits gained from working on the study (useful for future recruitment of co-ordinators)…”
Section: Discussionmentioning
confidence: 99%